DEVELOPMENT OF LATENT FINGERPRINT USING SAND - Bunda, Hernan B (President University, 2024)
This research project comprises of two studies. Study 1 aimed to create a fingerprint powder derived from sand and evaluate its acceptability based on fineness, adhesiveness, color, flow, and sensitivity, using a descriptive research design and survey method for assessment. Study 2 aims to examine the visibility of latent fingerprints developed with sand powder, utilizing an experimental research design and a Randomized Complete Block Design (RCBD) methodology. A purposive sampling was used to select 25 faculty members from various universities and colleges in Region 6, as well as 5 fingerprint experts from the PNP Crime Laboratory, to serve as expert evaluators. The mean and standard deviation were used as descriptive statistics, and the ANOVA was the inferential statistics. SEM-EDS mapping result revealed sand powder comprises of selenium (0.84%), carbon (13.01%), calcium (36.85%), oxygen (49.78%), aluminum (0.95%), magnesium (0.56%), silicon (3.63%), and sodium (0.13%). Sand’s acceptability as a fingerprint powder, based on fineness, adhesiveness, color, flow, and sensitivity, was rated as very acceptable. The visibility of latent fingerprints developed using sand was also found to be very visible. No significant differences were noted between sand powder and commercial fingerprint powders when applied to non-porous surfaces such as glass, plastic bottles, ceramics, painted wood and doorknob.